2014
DOI: 10.7314/apjcp.2014.15.1.253
|View full text |Cite
|
Sign up to set email alerts
|

Haematologic Parameters in Metastatic Colorectal Cancer Patients Treated with Capecitabine Combination Therapy

Abstract: MCV showed significant increase in chemotherapy response groups (PR and SD). In addition, a significant decrease was observed for platelet count in chemotherapy response groups. While NLR decrease was seen in only a PR group, PCT decrease was observed in all three groups. PCT and PLT values were higher in patients receiving Bevacizumab. Conclusions: PLT, PCT, MPV, and NLR values were decreased due to Capecitabinebased chemotherapy, however MCV was increased. PCT and PLT values were higher in patients who recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…In the study, patients were evaluated after 9 weeks and MCV elevation was found to be higher in the patients with complete and partial response (CR+PR) as compared to the patients with stable and progressive disease (SD+PD). Similar findings for response were noted for colorectal cancer cases (Inanc et al, 2014).However, in the present study, when the patients were grouped in the same manner, no significant difference was determined between the groups in terms of change in MCV. Arslan et al (2011) evaluated 75 metastatic breast cancer patients receiving capecitabine and found the median MCV difference (post-treatment values at nine week-baseline) to be 8.…”
Section: Discussionsupporting
confidence: 83%
“…In the study, patients were evaluated after 9 weeks and MCV elevation was found to be higher in the patients with complete and partial response (CR+PR) as compared to the patients with stable and progressive disease (SD+PD). Similar findings for response were noted for colorectal cancer cases (Inanc et al, 2014).However, in the present study, when the patients were grouped in the same manner, no significant difference was determined between the groups in terms of change in MCV. Arslan et al (2011) evaluated 75 metastatic breast cancer patients receiving capecitabine and found the median MCV difference (post-treatment values at nine week-baseline) to be 8.…”
Section: Discussionsupporting
confidence: 83%
“…10,12 This situation with different cytokines that have proinflammatory characteristics is very important for cancer patients. [18][19][20][21][22][23][24][25] However, Osada et al 18 reported that increased MPV level was very important in stomach cancer patients in compared with healthy subjects. 10,[12][13][14][15] Some studies did not find a relationship between MPV and platelet count as a prognostic factors in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…10,[12][13][14][15] Some studies did not find a relationship between MPV and platelet count as a prognostic factors in cancer patients. [18][19][20][21][22][23][24][25] However, Osada et al 18 reported that increased MPV level was very important in stomach cancer patients in compared with healthy subjects. Increased MPV in patients with gastric cancer have a relationship with p-selectin, which is an important indicator of platelet activation in thrombocyte surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer remains a significant problem for global health as it is one of the most common cause of tumorrelated death world-wide (Fouz et al, 2013;Engin et al, 2013;Sedighi et al, 2013;Zhu et al, 2013;Wu et al , 2014;Cabuk et al, 2014;Chin et al, 2014;Fouladi et al, 2014;Majeed et al, 2014;Gogia et al, 2014;Liu et al, 2014;Louisa et al, 2014;Moazzezy et al, 2014;Niu et al, 2014;Rizalar et al, 2014;Sipetic-Grujicic et al, 2014;Prajoko et al, 2014;Inanc et al, 2014;Varol et al, 2014;Yadav et al, 2014). Pemetrexed is a novel multitargeted antifolate that inhibits several enzymes in the de novo pathways of pyrimidine and purine biosynthesis, including thymidylate synthase, dihydrofolate reductase, and glycinamide ribonucleotide ormyltransferase.…”
Section: Discussionmentioning
confidence: 99%